Enhanced security model and efficient construction for direct anonymous attestation. (2017) - Yue, Xiaohan; Zhou, Fucai; Wang, Xibo; Li, Rui
Direct anonymous attestation (DAA) is a cryptographic scheme which enables the remote authentication of a trusted platform whilst preserving privacy under the user's control. In this paper, we first present the enhanced security model for DAA, in which more precise security notions demanded from DAA are defined than that in any previous model. Then we propose a novel approach for constructing an efficient DAA scheme: we design a secure two-party computation protocol for the join/issue protocol of DAA, and construct the DAA scheme concretely under the q-SDH assumption, DL assumption and XDH assumption. Based on the enhanced security model, we prove that our DAA scheme meets user-controlled anonymity, user-controlled traceability and non-frameability in the random oracle model. Finally, compared with other existing DAA schemes, our DAA scheme has better performance.